Motivation to learn ICT among senior public service officials in Malaysia : a conceptual framework - Hussein, Ramlah; Hashim, Junaidah; Abdul rahman , Rozailin (2010)

(untitled)
The paper aims to investigate the individual and situational factors that are believed to influence motivation to learn ICT among public senior officials in the Malaysian government. Based on Colquitt et al (2000) theoretical framework, a conceptual model was proposed to show the relationship between the factors investigated. Five factors, namely, self-efficacy, computer anxiety, valence of outcomes, internal locus control and climate of transfer were believed to influence motivation to learn ICT. One factor, resistance to change, was believed to moderate the relationship between the five factors and the motivation to learn ICT. Proposed research methodology in conducting the study was also discussed.